Réponses

2014-05-04T21:21:57+02:00
'Lut.


Exo 67:
1) D=(2x+3)²+(2x+3)(7x-2)
=(4x²+6x+6x+9)+(7x²-4x+21x-6)
=(4x²+12x+9)+(14x²+17x-6)
=18x²+29x+3
2) D=(2x+3)²+(2x+3)(7x-2) donne une fois factorisé (2x+3)[(2x+3)+(7x-2)]
3) D=(2x+3)[(2x+3)+(7x-2)] avec x=-4.
D=(2*-4+3)[(2*-4+3)+(7*-4-2)]
=(-8+3)[(-8+3)+(-28-2)]
=-5(-5-30)
=-5*-35
=5*35
=175



Exo 68:
1) E=(3x+2)²-(5-2x)(3x+2)
=9x²+12x+4-(15x+10-6x²-4x)
=9x²+12x+4-15x-10+6x²+4x
=15x²+x-6
2) E=(3x+2)²-(5-2x)(3x+2) donne une fois factorisé (3x+2)[(3x+2)-(5-2x)]
3) E=(3x+2)[(3x+2)-(5-2x)] avec x=-2
E=(3*-2+2)[(3*-2+2)-(5-2*-2)]
=(-6+2)[(-6+2)-(5+4)]
=-4(-4-9)
=-4*-13
=4*13
=52